1. Start by distributing the -2 on the left side of the equation: -8x - 16 + 2x = -5x + 10
2. Combine like terms on both sides: -8x + 2x - 16 = -5x + 10
3. Simplify the equation: -6x - 16 = -5x + 10
4. Move all the x terms to one side of the equation: -6x + 5x = 10 + 16
5. Combine like terms on both sides: -x = 26
6. Divide both sides of the equation by -1 to solve for x: x = -26.
Put the steps in order for solving the equation: −2(4x+8)+2x = −5x+10
(
9 answers
A student solves the following problem: 2(x - 2) + 5x = 24
Step 1: 2x - 4 + 5x = 24
Step 2: 10x - 4 = 24
Step 3: 10x - 4 + 4 = 24 + 4
Step 4: 10x = 28
Step 5: 10x/10=28/10
Step 6: x = 2.8
Where is the mistake? What did the student do incorrectly?
Step 1: 2x - 4 + 5x = 24
Step 2: 10x - 4 = 24
Step 3: 10x - 4 + 4 = 24 + 4
Step 4: 10x = 28
Step 5: 10x/10=28/10
Step 6: x = 2.8
Where is the mistake? What did the student do incorrectly?
The mistake is in Step 3. The student incorrectly added 4 to both sides of the equation instead of subtracting 4 from both sides.
The correct step 3 should be: 10x - 4 - 4 = 24 - 4
This would result in: 10x - 8 = 20
The correct step 3 should be: 10x - 4 - 4 = 24 - 4
This would result in: 10x - 8 = 20
To solve the equation: 24(34+x)=1,200
, give the reasons for each of the given steps.
What was done to the previous step to get to the current equation?
Step 1: 816+24x=1,200
Step 2: 816−816+24x=1,200 − 816
Step 3: 24x=384
Step 4: x=1
, give the reasons for each of the given steps.
What was done to the previous step to get to the current equation?
Step 1: 816+24x=1,200
Step 2: 816−816+24x=1,200 − 816
Step 3: 24x=384
Step 4: x=1
Step 1: 816+24x=1,200
To get to step 1, the equation was simplified by distributing 24 to both terms inside the parentheses.
Step 2: 816−816+24x=1,200 − 816
To get to step 2, 816 was subtracted from both sides of the equation in order to isolate the term with 24x.
Step 3: 24x=384
To get to step 3, the terms on the left side of the equation were combined by subtracting 816 from 816, resulting in 0.
Step 4: x=1
To get to step 4, both sides of the equation were simplified by dividing by 24 to solve for x.
To get to step 1, the equation was simplified by distributing 24 to both terms inside the parentheses.
Step 2: 816−816+24x=1,200 − 816
To get to step 2, 816 was subtracted from both sides of the equation in order to isolate the term with 24x.
Step 3: 24x=384
To get to step 3, the terms on the left side of the equation were combined by subtracting 816 from 816, resulting in 0.
Step 4: x=1
To get to step 4, both sides of the equation were simplified by dividing by 24 to solve for x.
2 of 52 of 5 Items
Question
To solve the equation: 24(34+x)=1,200
, give the reasons for each of the given steps.
What was done to the previous step to get to the current equation?
.
Step 1: 816+24x=1,200
Step 2: 816−816+24x=1,200 − 816
Step 3: 24x=384
Step 4: x=16
Question
To solve the equation: 24(34+x)=1,200
, give the reasons for each of the given steps.
What was done to the previous step to get to the current equation?
.
Step 1: 816+24x=1,200
Step 2: 816−816+24x=1,200 − 816
Step 3: 24x=384
Step 4: x=16
Step 1: 816+24x=1,200
To get to step 1, the equation was simplified by multiplying 24 with 34+x.
Step 2: 816−816+24x=1,200 − 816
To get to step 2, 816 was subtracted from both sides of the equation in order to isolate the term with 24x.
Step 3: 24x=384
To get to step 3, the terms on the left side of the equation were combined by subtracting 816 from 816, resulting in 0.
Step 4: x=16
To get to step 4, both sides of the equation were simplified by dividing by 24 to solve for x.
To get to step 1, the equation was simplified by multiplying 24 with 34+x.
Step 2: 816−816+24x=1,200 − 816
To get to step 2, 816 was subtracted from both sides of the equation in order to isolate the term with 24x.
Step 3: 24x=384
To get to step 3, the terms on the left side of the equation were combined by subtracting 816 from 816, resulting in 0.
Step 4: x=16
To get to step 4, both sides of the equation were simplified by dividing by 24 to solve for x.
Simplify: −4(2x+5)
(−4−2x)+(−4−5)
(−4+2x)×(−4+5)
(−4×2x)+(−4×5)
(−4÷2x)+(−4÷5
(−4−2x)+(−4−5)
(−4+2x)×(−4+5)
(−4×2x)+(−4×5)
(−4÷2x)+(−4÷5
−4(2x + 5) simplifies to -8x - 20.
(−4−2x) + (−4−5) simplifies to -8 - 2x - 9 which further simplifies to -17 - 2x.
(−4+2x) × (−4+5) simplifies to (-4 + 2x) × 1 which further simplifies to -4 + 2x.
(−4 × 2x) + (−4 × 5) simplifies to -8x - 20.
(−4 ÷ 2x) + (−4 ÷ 5) does not simplify as it involves division of variables.
(−4−2x) + (−4−5) simplifies to -8 - 2x - 9 which further simplifies to -17 - 2x.
(−4+2x) × (−4+5) simplifies to (-4 + 2x) × 1 which further simplifies to -4 + 2x.
(−4 × 2x) + (−4 × 5) simplifies to -8x - 20.
(−4 ÷ 2x) + (−4 ÷ 5) does not simplify as it involves division of variables.